Anti-SARS-CoV-2 Revaccination Success in Kidney Transplant Recipients With No Initial Humoral Response Is Linked to Primary Vaccine Type - Stumpf, Julian; Schwöbel, Jörg; Karger, Claudia; Schirutschke, Holger; Mauer, René; Klimova, Anna; Tonn, Torsten; Hugo, Christian (Frontiers in Medicine, 2022)
Background: While anti-SARS-CoV-2 vaccination success in kidney transplant recipients (KTR) after two doses 1273-mRNA was associated with higher seroconversion rates compared to BNT162b2-mRNA, in our “DIA-Vacc Study” (NCT04799808), it remains unclear whether this may also be the case in nonresponding KTR after a third vaccination dose. Methods: Nonresponding KTR (after two mRNA vaccinations) were investigated 4.5 to 6 months after study enrollment at first vaccination. 166/193 received a third vaccination between month 3.5 and five after initial study enrollment and were always investigated four weeks later, exploring humoral immune (ELISA) and specific cellular responses (interferon-γ release assay). 67/193 measurements in KTR were done immediately before third vaccination or in KTR without further vaccination at 4.5 to 6 months. Results: Of 193 KTR with no initial immune response 4 weeks after second vaccination, 106/87 were immunized twice with 1273-mRNA/BNT162b2-mRNA, respectively. Additional mRNA booster vaccination led to positive seroconversion rates of 30% to 50%, while 16% of the initial nonresponders demonstrated a delayed seroconversion without any booster vaccination. Using logistic regression analysis, a positive IgG response after third vaccination was 23% more likely if primary vaccine type was 1273-mRNA compared to BNT162b2-mRNA (OR = 4.420, 95 % CI [1.208 - 16.173], p = 0.025). Apart from primary vaccine type, a weak (3.2 – 35.2 BAU/ml) anti-SpikeS1 IgG response 4 weeks after second vaccination (p < 0.001) and lack of MMF/MPA as part of the immunosuppressive treatment (trend, p =0.06), no other variables studied correlated with seroconversion success. In conclusion, this study adds important evidence towards using 1273-mRNA as primary mRNA vaccine type for immunosuppressed KTR.